Challenges faced by organized smallholder in Felda Lakum toward MSPO implementation / Mohamad Afiq Nadzri - Nadzri, Mohamad Afiq (Faculty of Plantation and Agrotechnology, 2019)
Palm oil production is importance for the economy of Malaysia as the world’s second largest producer of the commodity after Indonesia. Today, 5.81 million hectares of land in Malaysia is under oil palm cultivation. Producing 19.91 million tons of palm oil and 4.95 tons of palm kernel oil. In order to achieve sustainability in oil palm plantation, the Malaysian Sustainable Palm Oil (MSPO) were introduce to promote high quality production and increase profitable of oil palm grower in Malaysia. The aim of this study to investigate the challenges factor among organized smallholder towards MSPO practices and to identify which factor is limiting group of organized smallholders to understand MSPO. This study had been done at Pahang which 108 organized smallholders were involve in this collected data process. The data were analyzed by using SPSS on independent variable, knowledge, finance and interest meanwhile for dependent variable is the challenge of MSPO. The result can be determined by using Pearson’s Correlation and Multiple Linear Regression which importance to identified the most significant factor of this study. Through Pearson’s Correlation, knowledge is the most positive strong relationships with the challenge of MSPO with the coefficient reading 0.688. Other factor such as finance and interest also shown significant relation with the challenge of MSPO but the most dominant among them is knowledge factor which can be conclude as barrier to organized smallholders to certificate.